Abscisic Acid: Role in Fruit Development and Ripening - Gupta, Kapil; Wani, Shabir H.; Razzaq, Ali; Skalicky, Milan; Samantara, Kajal; Gupta, Shubhra; Pandita, Deepu; Goel, Sonia; Grewal, Sapna; Hejnak, Vaclav; Shiv, Aalok; El-Sabrout, Ahmed M.; et al. (Frontiers in Plant Science, 2022)
Abscisic acid (ABA) is a plant growth regulator known for its functions, especially in seed maturation, adaptive responses to biotic and abiotic stresses, leaf and bud abscission, and seed dormancy. ABA activity is governed by multiple regulatory pathways that control ABA biosynthesis, signal transduction, and transport. Transport of the ABA signaling molecule occurs from the shoot (site of synthesis) to the fruit (site of action), where ABA receptors decode information as fruit maturation begins and is significantly promoted. The maximum amount of ABA is exported by the phloem from developing fruits during seed formation and initiation of fruit expansion. In the later stages of fruit ripening, ABA export from the phloem decreases significantly, leading to an accumulation of ABA in ripening fruit. Fruit growth, ripening, and senescence are under the control of ABA, and the mechanisms governing these processes are still emerging. During the ripening phase of fruit ripening, interactions between ABA and ethylene are found in both climacteric and non-climacteric fruit. It is clear that ABA regulates ethylene biosynthesis and signaling during fruit ripening, but the molecular mechanism of the interaction between ABA and ethylene has not yet been discovered. The effects of ABA and ethylene on fruit ripening are synergistic, and the interaction of ABA with other plant hormones is an essential determinant of fruit growth and ripening. Reaction and biosynthetic mechanisms and signal transduction and recognition of ABA receptors in fruits need to be elucidated by a more thorough study to understand the role of ABA in fruit ripening. Genetic modifications of ABA signaling can be used in commercial applications to increase fruit yield and quality. This review discusses the mechanism of ABA biosynthesis, its translocation, signaling pathways, as well as recent findings on ABA function in fruit development and ripening.